QTL mapping for seedling and adult plant resistance to stripe and leaf rust in two winter wheat populations - Kokhmetova, Alma; Rathan, Nagenahalli Dharmegowda; Sehgal, Deepmala; Malysheva, Angelina; Kumarbayeva, Madina; Nurzhuma, Makpal; Bolatbekova, Ardak; Krishnappa, Gopalareddy; Gultyaeva, Elena; Kokhmetova, Asia; Keishilov, Zhenis; Bakhytuly, Kanat (Frontiers in Genetics, 2023)
The two recombinant inbred lines (RIL) populations developed by crossing Almaly × Avocet S (206 RILs) and Almaly × Anza (162 RILs) were used to detect the novel genomic regions associated with adult plant resistance (APR) and seedling or all-stage resistance (ASR) to yellow rust (YR) and leaf rust (LR). The QTLs were detected through multi-year phenotypic evaluations (2018 to 2020) and using high throughput DArTseq genotyping technology. Both the populations were evaluated for YR APR in two environments (2018 and 2019) and LR APR in three environments (2018, 2019, and 2020) in Anza population and two environments (2018 and 2019) in Avocet population; both the populations were phenotyped for one environment during 2020 for LR and YR ASR and genotyped using high throughput DArTseq technology. RILs exhibited significant genetic variation with p<0.001 and coefficient of variation ranged from 9.79 to 47.99% for both LR and YR in all environmental and stages of evaluations. Also, the heritability is quite high and ranged between 0.47 -0.98. We identified nine stable QTLs for YR APR on chromosome 1B,